Strategic shifts in armed groups from armed action to political action (Badr Organization) - Alasaker, Fahad Abdul Rahman Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The research relied on the transformation of the "Badr" Organization from military action to political action, in addition to the main transformation influences on the organization. The research is divided into two main parts: The first part discussed the “Badr Organization”; its history and military operations, whether in the armed action times or after the transformation. This part aimed to know the organization leaders and their position in the Iraqi government, to know the organization adopted ideology, and to know organization distribution. The second part discussed the organization transformation from military action to political action, the dimensions of this transformation at the behavioral, organizational, and ideological level, the impact of the internal environment in Iraq and the external environment (the war in Syria) on the “Badr” organization, and the path of the political transformation.